2005
DOI: 10.1002/bit.20589
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH change on the performance and microbial community of enhanced biological phosphate removal process

Abstract: An acetate-rich wastewater, containing 170 mg/L of total organic carbon (TOC), 13 mg/L of N, and 15 mg/L of P, was treated using the enhanced biological phosphate removal (EBPR) process operated in a sequencing batch reactor. A slight change of pH of the mixed liquor from 7.0 to 6.5 led to a complete loss of phosphate-removing capability and a drastic change of microbial populations. The process steadily removed 94% of TOC and 99.9% of P from the wastewater at pH 7.0, but only 93% TOC and 17% of P 14 days afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 48 publications
1
14
1
Order By: Relevance
“…To simulate dynamic behaviors of the RAAO process at different temperatures, a pre-compiled and modified version of ASM2d in WEST 3.7.5, ASM2dTemp, was adopted with temperature correction for the biological carbon, nitrogen and phosphorus removal. Considering the high pH values in the influent ( Table 2) and effluent (7.60±0.11) of the RAAO process, the metabolisms model of glycogen accumulating organisms (GAOs) was not incorporated into the ASM2dTemp model since phosphorus accumulating organisms (PAOs, X PAO ) usually grow dominantly and GAOs wash out in the pH-uncontrolled condition [24] and the condition with pH higher than 7.25 [25,26]. The clarification-thickening process in the secondary clarifier was modeled according to the onedimensional model by Takács et al [27], and the double-exponential model was used to describe the settling velocity of activated sludge, as shown in Eq.…”
Section: Models and Simulation Environmentmentioning
confidence: 99%
“…To simulate dynamic behaviors of the RAAO process at different temperatures, a pre-compiled and modified version of ASM2d in WEST 3.7.5, ASM2dTemp, was adopted with temperature correction for the biological carbon, nitrogen and phosphorus removal. Considering the high pH values in the influent ( Table 2) and effluent (7.60±0.11) of the RAAO process, the metabolisms model of glycogen accumulating organisms (GAOs) was not incorporated into the ASM2dTemp model since phosphorus accumulating organisms (PAOs, X PAO ) usually grow dominantly and GAOs wash out in the pH-uncontrolled condition [24] and the condition with pH higher than 7.25 [25,26]. The clarification-thickening process in the secondary clarifier was modeled according to the onedimensional model by Takács et al [27], and the double-exponential model was used to describe the settling velocity of activated sludge, as shown in Eq.…”
Section: Models and Simulation Environmentmentioning
confidence: 99%
“…With the exception of the D. vanus sequence all the 16S rRNA data available for clusters I and II Defluviicoccus were obtained from lab scale reactors fed either amino acids and/or simple fatty acids (McMahon et al, 2002;Wong et al, 2004;Zhang et al, 2005;Meyer et al, 2006;Wong and Liu, 2007;McIlroy et al, submitted). Even with such a reactor containing almost all alphaproteobacterial TFO, Oehman et al (2006) showed only 16% of its biomass hybridized with the existing Defluviicoccus probes or other probes designed to target known alphaproteobacterial TFO.…”
mentioning
confidence: 99%
“…After two months recovery, the P removal rose again to achieve over 80% at 182 nd d (sludge E). Similar pH-effect patterns on EBPR SBR performance have been vigorously studied [32, 57], but the drastic change of microbial population have not been fully uncovered due to certain limitations of molecular technologies and EBPR-related microbial information at that time. In order to reveal the microbial structure variation in the community, DNA samples from A—E were extracted in triplicate for 16S rRNA gene pyrosequencing.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the acidic pH in the aerobic zone will inhibit the growth of PAOs due to the proliferation of GAOs in the EBPR system, resulting in deteriorated EBPR system [28]. It’s been reported that a slight change of pH from 7.0 to 6.5 had led to EBPR deterioration and a drastic change of microbial populations in a SBR [32]. …”
Section: Introductionmentioning
confidence: 99%